Science-policy interactions for climate-smart agriculture uptake: lessons learnt from national science-policy dialogue platforms in West Africa - Zougmoré, Robert B.; Partey, Samuel T.; Totin, Edmond; Ouédraogo, Mathieu; Thornton, Philip K.; Karbo, Naaminong; Sogoba, Bougouna; Dieye, Bounama (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Science–policy interfaces are critical in shaping agricultural and environmental governance. However, connecting science with policy has always been a challenge for both scientists and policymakers. In Ghana, Mali and Senegal, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) supported the creation of a multi-stakeholder national science-policy dialogue platforms on climate-smart agriculture (NSPDP-CSA) to use scientific evidence to create awareness on climate change impacts on agriculture and advocate for the mainstreaming of climate change and climate-smart agriculture (CSA) into agricultural development plans. Since their establishment, there is limited information as to how the modes of operation and achievements of the NSPDP-CSA improve our understanding of the sciencepolicy interfaces of agricultural and climate change decision making. This study aimed to use the evidence from the operations and achievements of the NSPDP-CSA to make recommendations for effective science-policy interaction on climate change and CSA. We used semi-structured questionnaire interviews and review of technical reports produced by the platforms to obtaining the information aforementioned. The results showed that using NSPDPCSA may be an innovative approach to effectively engaging policymakers/decision-makers for climate change and CSA mainstreaming into agricultural development policies and plans in Ghana, Mali and Senegal. For effective science-policy interaction, the study suggests the following recommendations: (a) Institutionalising the NSPDP-CSA through embedding them within national institutions improves their credibility, relevance and legitimacy among policymakers; (b) two-way communication may have a phenomenal advantage in the codevelopment of solutions that address climate change vulnerabilities and impacts; and (c) using relevant communication products and packaging CSA and climate change with evidence to align with country priorities will facilitate readily uptake in policy decision-makings. A framework of operation for the platforms was suggested based on lessons learnt from the 3 countries’ experiences and achievements.